2014
DOI: 10.1371/journal.pone.0106121
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Pharyngeal Phase of Swallow in the Cat

Abstract: ObjectiveThe pharyngeal phase of swallow has been thought to be a stereotypical motor behavior.Study DesignThis is a prospective, preclinical, hypothesis driven, one group by three-task design.MethodsWe sought to compare the effects of pharyngeal swabbing, water only, and water plus punctate mechanical stimulation on the spatiotemporal features of the pharyngeal phase of swallow in the cat. Swallow was elicited under these three conditions in six anaesthetized cats. Electromyographic activity was recorded from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 80 publications
1
27
2
Order By: Relevance
“…The results of this study further support our hypothesis that there are different central mechanisms for regulating swallow amplitude and duration. Clinically, it has been assumed that swallow duration positively correlates with force production, as defined by swallow phase relationships in videofluoroscopy exams [13]. We have now established that swallow-related EMG amplitude and duration are not correlated in cats [13,46,73], humans [74,75], or rats (present study).…”
Section: Emg Amplitude and Duration Are Not Correlatedmentioning
confidence: 46%
See 1 more Smart Citation
“…The results of this study further support our hypothesis that there are different central mechanisms for regulating swallow amplitude and duration. Clinically, it has been assumed that swallow duration positively correlates with force production, as defined by swallow phase relationships in videofluoroscopy exams [13]. We have now established that swallow-related EMG amplitude and duration are not correlated in cats [13,46,73], humans [74,75], or rats (present study).…”
Section: Emg Amplitude and Duration Are Not Correlatedmentioning
confidence: 46%
“…These pivotal studies form a foundation for the swallow field, and since then swallow has been studied in vivo in the mouse [9], rat [10,11], bat [12], cat [13][14][15][16][17][18][19], rabbit [20,21], pig [22], sheep [23], goat [24], monkey [25,26], and human [27][28][29][30][31]. Swallow has also been studied in situ [19,[32][33][34] and in vitro [35] and modeled in silico [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Spearman et al . () reported that spatiotemporal control of swallowing‐related muscle activity was modified by sensory feedback from mechanoreceptors in anaesthetized cats. Although swallowing‐related muscle activity was not changed by benzamil application, we should consider the possibility of modulation of swallowing motor activity by amiloride analogues.…”
Section: Discussionmentioning
confidence: 99%
“…Jafari et al (2003) suggested that the afferent signals from the internal branch of the SLN, which contains afferents from the supraglottic larynx and epiglottis, play an important role in normal swallowing, particularly in facilitating laryngeal closure during swallowing. Additionally, Spearman et al (2014) reported that spatiotemporal control of swallowing-related muscle activity was modified by sensory feedback from mechanoreceptors in anaesthetized cats. Although swallowing-related muscle activity was not changed by benzamil application, we should consider the possibility of modulation of swallowing motor activity by amiloride analogues.…”
Section: Discussionmentioning
confidence: 99%
“…Eight muscles were used to evaluate swallow occurrence: mylohyoid, geniohyoid, thyrohyoid, thyropharyngeus, thyroarytenoid, cricopharyngeus, parasternal, and costal diaphragm. These muscles span the actions during the pharyngeal phase of swallow: a) mylohyoid, geniohyoid and thyrohyoid for hyolaryngeal elevation; b) thyropharyngeus for inferior pharyngeal constrictor; c) cricopharyngeus for upper esophageal sphincter regulation; d) thyroarytenoid for laryngeal adduction; and e) parasternal and costal diaphragm for inspiratory activity [ 12 , 13 , 15 , 24 ].…”
Section: Methodsmentioning
confidence: 99%